Diasporic Responses: Identity, Culture, and Female Bonding in Bharti Mukherjees Desirable Daughter - Nida Zainab; Dr. Namita Chouhan (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Bharati Mukherjee, an immigrant Indian writer, has played a notable role in the escalation of Indian English Writing with her notable works. The prime premise of her works is the issues encountered by women in their foreign atmosphere. Mukherjees amalgamation of two cultures has given her a true outlook of traditional Indian and contemporary American way of life which she inturn has given to the readers through her works. Being an immigrant writer she unveils the topics, diaspora, assimilation, cultural conflicts, immigration, quest for self actualisation and identity. Most of her protagonists strive hard for their identity in the native as well as foreign land. This paper presents a thematic analysis of the novel Desirable Daughters by Bharati Mukherjee. The story navigates the complex tapestry of identity, cultural assimilation, and the pursuit of self-discovery among IndianAmerican characters. Through a qualitative thematic approach, this analysis delves into the multidimensional facets of the characters experiences, exploring themes such as diaspora, gender roles, tradition, modernity, and the clash of cultures. The protagonists face the dilemma of the modern world when they are involved with American life. Two of the three sisters change from an Indian desirable daughter to a free Indian-American woman. They are caught between past and present, tradition and modernity. They can break several traditional norms and codes, however, they do not separate themselves from Indian norms. This study scrutinizes each female protagonist through the lens of the post-colonial transcultural theories primarily by Stuart Hall and Homi Bhabha. The analysis aims to shed light on the intricacies of cultural adaptation, the impact of historical legacies on personal identity, and the challenges of reconciling diverse cultural elements within the context of the lives of the characters.